2013
DOI: 10.2478/johh-2013-0026
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Near-Bed Turbulence Structures Influence on the Initiation of Saltating Grains Movement

Abstract: Abstract:The focus of this paper is on the analysis of the influence of near-bed turbulence structures with the inclusion of existing coherent structures on the entrainment of saltating particles in a water stream from the Lagrangian perspective. The interactions between turbulence structures and initiation of particles movement is the key for better understanding of the physics of sediment transport and particles behaviour. These aims are addressed by use of a 3D relevant model of spherical saltating particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The first regime, corresponding to continuous particle motion between collisions with the bed, is superdiffusive with γ x ,γ y > 0.50, and the initiation of movement when particles are subject to acceleration takes place for tu*/d ≤ 3. This is in agreement with the threshold found by Bialik et al () through the application of a turbulent structures generator that discriminated between the near‐field and ballistic subranges (Bialik, ), and close to the threshold observed by Campagnol et al (), tu*/d = 1.5–2.5. Within this region the longitudinal diffusive scaling coefficient indicates a superballistic regime, 1.0 < γ x < 2.0, with exponents dependent on transport conditions and bed material.…”
Section: Discussion: Temporal and Spatial Scales Of Diffusive Regimessupporting
confidence: 92%
“…The first regime, corresponding to continuous particle motion between collisions with the bed, is superdiffusive with γ x ,γ y > 0.50, and the initiation of movement when particles are subject to acceleration takes place for tu*/d ≤ 3. This is in agreement with the threshold found by Bialik et al () through the application of a turbulent structures generator that discriminated between the near‐field and ballistic subranges (Bialik, ), and close to the threshold observed by Campagnol et al (), tu*/d = 1.5–2.5. Within this region the longitudinal diffusive scaling coefficient indicates a superballistic regime, 1.0 < γ x < 2.0, with exponents dependent on transport conditions and bed material.…”
Section: Discussion: Temporal and Spatial Scales Of Diffusive Regimessupporting
confidence: 92%
“…Their impact in a particular phase of the particles' movement determines the shape of the particles' trajectory. Particularly striking is the dominant role of the sweeps events in the initial motion of the grains, which was confirmed by experimental (Cameron 2006) and numerical (Bialik 2013) studies. The negative values of the vertical velocity decrease the lift force and should thus reduce the entrainment, but the results of simulations and experiments indicate a completely different role of sweeps events.…”
Section: Initiation Of Saltating Grains Movementsupporting
confidence: 54%
“…Moreover, the results suggested that ejections have the smallest part in this process. More details on the quadrant analysis technique and the results can be found in Bialik (2013).…”
Section: Initiation Of Saltating Grains Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) is supplemented with a trajectory equation, bed-collision sub-model based on the impulse momentum equations, and a Monte-Carlo generator of flow velocity field, initially proposed in [16] and later also used to simulate saltating grains movement in a 2D model [2]. The model equations can easily be solved numerically using the fourth-order Runge-Kutta method and employing the following initial conditions [3,4]:…”
Section: Introductionmentioning
confidence: 99%